Synthesis of N-heterocyclic carbene (NHC)-Au/Ag/Cu benzotriazolyl complexes and their catalytic activity in propargylamide cycloisomerization and carbonyl hydrosilylation reactions - Kaplanai, Entzy; Tzouras, Nikolaos V.; Tsoureas, Nikolaos; Bracho Pozsoni, Nestor; Bhandary, Subhrajyoti; Van Hecke, Kristof; Nolan, Steven P.; Georgios C. Vougioukalakis (Dalton Transactions, 2024)
Carbene-metal-amide (CMA) complexes of gold, silver, and copper have been studied extensively for their photochemical/photocatalytic properties and as potential (pre-)catalysts in organic synthesis. Herein, the design, synthesis, and characterization of five bench-stable Au-, Ag-, and Cu-NHC complexes bearing the benzotriazolyl anion as an amide donor, are reported. All complexes are synthesized in a facile and straightforward manner, using mild conditions. The catalytic activity of the Ag and Cu complexes was studied in propargylamide cycloisomerization and carbonyl hydrosilylation reactions. Both CMA-catalyzed transformations proceed under mild conditions and are highly efficient for a range of propargylamides and carbonyl compounds, respectively, affording the desired corresponding products in good to excellent yields.